1986
DOI: 10.1139/t86-081
|View full text |Cite
|
Sign up to set email alerts
|

Creep behaviour of undisturbed clay permafrost

Abstract: An in situ analysis of naturally occurring creep has been carried out at the proposed Canadian Arctic Gas pipeline crossing of Great Bear River in the Northwest Territories. This is the last of four papers that describe the study. Creep properties of natural and reconstituted frozen soils are briefly reviewed. A laboratory programme to measure creep properties of undisturbed ice-rich glaciolacustrine clay samples from the Great Bear River site is described in detail. The results are analysed to determine empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…A mass of dirty ice or ice‐rich debris on a slope would be rigid near the surface, but as deviatoric stress increased with depth, the threshold would eventually by surpassed and intense localized shear could occur. This is consistent with many of the observations of pluglike flow in rock glaciers and permafrost slopes reviewed above [ Savigny and Morgenstern , ; Haeberli et al, ]. Dirty basal ice at the bottom of a glacier might be expected, therefore, to accommodate a large fraction of the glacier's motion, particularly where the dirty ice is close to the melting temperature and the overlying ice is cold, as was the case at Urumqi Glacier [ Echelmeyer and Zhongxiang , ].…”
Section: Summary and Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…A mass of dirty ice or ice‐rich debris on a slope would be rigid near the surface, but as deviatoric stress increased with depth, the threshold would eventually by surpassed and intense localized shear could occur. This is consistent with many of the observations of pluglike flow in rock glaciers and permafrost slopes reviewed above [ Savigny and Morgenstern , ; Haeberli et al, ]. Dirty basal ice at the bottom of a glacier might be expected, therefore, to accommodate a large fraction of the glacier's motion, particularly where the dirty ice is close to the melting temperature and the overlying ice is cold, as was the case at Urumqi Glacier [ Echelmeyer and Zhongxiang , ].…”
Section: Summary and Implicationssupporting
confidence: 85%
“…For example, landslides and creep in frozen stratified riverbank materials in northern Canada and Alaska were investigated by McRoberts and Morgenstern [], Savigny and Morgenstern [], and Darrow and others [ Darrow et al, ]. In each of these studies, localized slip displacement was found to occur at depth in fine‐grained strata with high unfrozen water content, while in the latter two studies, extensive distributed creep dominated in ice‐rich strata [ Savigny and Morgenstern , , ; Darrow et al, ]. An inclinometry study of deformation of frozen slopes of the Tibetan Plateau also showed distributed creep occurring within ice‐rich soil, and deformation data approximately matched a power law constitutive relation like that used for pure ice [ Wang and French , ].…”
Section: Field Observationsmentioning
confidence: 99%
“…Many types of laboratory tests, for example shearing in axial compression (AC) at CSR, or maintaining CSC, to measure the resulting creep deformations, or under given strain modes, have been performed on frozen soils or Arctic permafrost (Goughnour and Andersland 1968;Sayles 1974;Parameswaran and Jones 1981;Weaver and Morgenstern 1981;Savigny and Morgenstern 1986;Vyalov et al 1989;Ladanyi 1997) to advance and verify theoretical models. Microstructural aspects have been examined and quantified to establish their influence on mechanical properties by Cole (2001).…”
Section: Laboratory Stress Path Testing Equipmentmentioning
confidence: 99%
“…The parameter A for in situ deformation of glacier ice would be even lower than the Paterson's value [e.g., Hubbard et al , 1998; Gudmundsson , 1999]. The A values for ice‐supersaturated fine soil under steady state creep hardly exceed those of polycrystalline ice [e.g., McRoberts et al , 1978; Savigny and Morgenstern , 1986]. In addition, an increase in debris content strengthens the frozen soil owing to interlocking of soil particles larger than sand size [e.g., Hooke et al , 1972; Nickling and Bennett , 1984].…”
Section: Factors Affecting Deformation Of Ice‐debris Mixturementioning
confidence: 99%